Comparison of carotenoid accumulation and biosynthetic gene expression between Valencia and Rohde Red Valencia sweet oranges - Wei, Xu (Plant science : an international journal of experimental plant biology, 2014)
Copyright © 2014 Elsevier Ireland Ltd. All rights reserved.